Path analysis of farmer knowledge, attitudes, and practices toward lumpy skin disease in beef cattle - Sohrab Khan; Darawan Addoddon; Jutamas Prapapanpong; Minta Suwannaboon; Orapun Arjkumpa; Kannika Na-Lampang; Warangkhana Chaisowwong; Supitchaya Srisawang; Veerasak Punyapornwithaya (Animal Diseases, 2025)
Abstract Lumpy skin disease (LSD) poses a significant threat to cattle populations and the livelihoods of farmers in Thailand. This study uses path analysis to explore the interrelationships among the knowledge, attitudes, and practices (KAP) of beef cattle farmers regarding LSD. A total of 384 farmers provided data on their sociodemographic characteristics and responses to KAP-related questions. Path analysis was employed to examine how KAP components interact and how demographic factors influence these relationships. The analysis revealed strong positive relationships between farmers’ knowledge and attitudes (β = 0.96, p < 0.001) and between attitudes and practices (β = 0.08, p < 0.008). Farmers with greater knowledge of LSD were more likely to adopt positive attitudes toward disease control and implement effective management practices. Additionally, knowledge had a direct influence on farmers’ practices (β = 0.38, p < 0.001), indicating that improved awareness of LSD is linked to better disease management. By strengthening knowledge, these efforts can positively influence attitudes and practices, leading to more effective control strategies. As the first KAP study on LSD in Thailand, this research highlights the critical role of targeted education programs in improving farmers’ understanding of LSD. Ultimately, enhancing disease management through education can help reduce the economic impact of LSD on Thailand’s livestock sector and promote sustainable farming practices.